Minimizing interference in unmanaged environments of densely deployed wireless access points using a graphical game model - Pitsillides, Andreas; Antoniou, Josephine; Papadopoulou, Vicky G.; Libman, Lavy (My University, 2012)
Urban residential areas are becoming increasingly dense with more and more wireless home networks being deployed in close proximity. Considering that in such a dense urban residential area, each unit has its own wireless access point (AP), deployed without any coordination with other such units, then a need arises for reducing interference and increasing overall Quality of Experience (QoE) of the clients involved. To do this, we propose that neighbouring APs i.e., APs that are physically close to each other form groups, where one member of the group serves the terminals of all group members in addition to its own terminals, while the other APs of the group can be silent or even turned off. The fact that participating units are deployed without any coordination makes the overall QoE vulnerable to the selfish behaviour of each unit. We propose a cooperative-neighbourhood graphical game model comprising of a network of selfishly-oriented nodes represented by a graph where the outgoing links of a certain node capture the improvement in utility that a neighbour's client may experience from a potential cooperation. We show and prove that using the proposed model provides motivation for APs to enter and remain in cooperative neighbourhoods, in which interference is decreased due to the voluntary cooperation of the neighbours.
Keywords: Close proximity; Game models; Group members; Overall quality; Potential cooperation; Residential areas; Voluntary cooperation; Wireless access points; Wireless home network; Ad hoc networks; Quality of service; Radio communication; Interference suppression